Coronary artery aneurysm in Loeys-Dietz syndrome: a case report. Issue 6 (13th May 2022) - Jost, Zachary T.; Sang, Charlie J.; Lertwilaiwittaya, Pongtawat; Chapman, Gregory D.
Abstract: Background: Loeys-Dietz syndrome (LDS) is a connective tissue disorder that commonly presents with vascular abnormalities. Owing to the rarity and severity of the condition, consensus guidelines for aortic surgery thresholds vary. In addition, evaluation of coronary arteries in patients with LDS (either routinely or before aortic root surgery) remain undefined. In this case report, we discuss a patient with LDS who found to have an ectatic aortic root and a coronary artery aneurysm and discuss guidelines for evaluation and management in this patient population. Case summary: A 48-year-old woman was incidentally found to have a 45 mm ectatic aortic root during evaluation for a neck mass. As part of pre-operative evaluation for aortic root replacement, left heart catheterization revealed a left main coronary artery aneurysm. Family history revealed aortic aneurysms, sudden cardiac death, and tall height. Physical examination was notable for pectus excavatum and elongated limbs. Workup for inflammatory aetiologies of aortic root dilation was negative. Genetic testing revealed a heterozygous pathogenic TGBF3 variant, consistent with LDS Type 5. She subsequently underwent two-vessel coronary artery bypass, excision of her left main coronary artery aneurysm, and ascending aortic replacement. Discussion: In this case, we describe a patient with LDS who was noted to have a coronary artery aneurysm, a rare finding in the initial presentation of disease. In addition, we examine guidelines regarding evaluation of management of aortic root disease and coronary aneurysms.